Human Relations in the Puranaanooru - P, Ganeshvadivel (International Research Journal of Tamil, 2022)
In the modern age, the relationship between human beings today is in a state of decline. Human relationships are not formed by love, character, or affection. They are formed on the basis of material and attachments, and on the basis of needs. Those who are able to get along with themselves will eventually be exposed to their true qualities and characteristics, just as a snake peels off its skin and leaves it, once the needs of their consciousness are fulfilled. Husband, wife, children, siblings, relatives, and blood relations are all relationships that have arisen to satisfy some kind of need. The friendship and social relationships formed when they leave the family and socialize in the community are chosen as a relationship that can be enjoyed by one’s own self-interest. Thus, today’s relationships are bound up only for money, position, and selfishness. However, in the Puranaanooru of Sangam literature, this study is carried forward to find out how the husband-wife relationship, the child relationship, the father-child relationship, the king-poet relationship, the king and people relationship, the poet-poet relationship, the places where the human relationship is established, the friendship mixed with the mind, etc., were presented in this study and carried forward to understand how they had the elements, commitments, and sacrifices of various human relationships.